Language Sample Analysis With TalkBank: An Update and Review - MacWhinney, Brian; Fromm, Davida (Frontiers in Communication, 2022)
This article presents state-of-the-art methods for coding, analyzing, and interpreting discourse-level language samples from children and adults with language disorders using the data, tools, and methods provided by the TalkBank system (https://talkbank.org). These open and free resources can be used for language sample analysis (LSA) for any clinical population (e.g., child language disorders, stuttering, aphasia, dementia, traumatic brain injury, right hemisphere brain damage), as well as for control participants without communication impairments. Here, we examine methods that use ASR (automatic speech recognition), NLP (natural language processing), database technology, statistics in R and Python, and ML (machine learning). These methods are used by tools for corpus analysis, LSA profiling, database searches, online browsing through transcripts linked to media, and a new system for online collaborative commentary. These tools and methods provide multimedia access to transcripts from a wide variety of participants with and without language disorders.